Follicular dendritic cell sarcoma in the right chest wall: A case report. Issue 35 (28th August 2020) - Xu, Hongli; Chen, Bin; Jiang, Chengwei; Yang, Zhaoying; Wang, Keren
Abstract: Rationale: Follicular dendritic cell sarcoma (FDCS) is a rare malignant tumor that originates from germinal center follicular dendritic cells, and can occur at both nodal and extranodal sites. There are very few described cases of FDCS arising in the chest wall. Patient concerns: A 44-year-old male patient presented with a history of right chest wall pain for 5 months. Diagnoses: Positron emission tomography/computed tomography showed a significant increase in 18 F-fluorodeoxyglucose uptake and multiple small axillary lymph nodes without hypermetabolic lesions. Immunohistochemistry results of a core-needle biopsy indicated FDCS, which was consistent with the postoperative pathological examination. Interventions: The patient underwent tumor resection with lymphadenectomy of level I axillary nodes. No metastasis in the lymph nodes was observed in the postoperative pathological examination. The patient did not accept chemotherapy or radiotherapy. Outcomes: After 18 months, the patient remains in good condition with no evidence of disease recurrence. Lessons: This report highlights a rare case of a FDCS arising in the chest wall. Accurate clinical diagnosis and staging of this rare malignant sarcoma is essential for the developmnt of effective treatment strategies. Preoperative 18 F-fluorodeoxyglucose positron emission tomography/computed tomography scanning combined with core-needle biopsy could provide differentiation between benign and malignant tumors, as well as lymph node involvement and metastatic status.